The impact of four widely used neonicotinoid insecticides on Tetragonisca angustula (Latreille) (Hymenoptera: Apidae) - Jacob, Cynthia Renata de Oliveira; Zanardi, Odimar Zanuzo; Malaquias, José Bruno; Souza Silva, Carina Aparecida; Yamamoto, Pedro Takao (Chemosphere (Oxford), 2019)
Application of neonicotinoid insecticides on crops can reduce the pollination services and population levels of the stingless bee Tetragonisca angustula (Latreille) (Hymenoptera: Apidae) in Neotropical agroecosystems. However, the impact of these insecticides on this bee has not been fully investigated. This study assessed the susceptibility levels of T. angustula to four neonicotinoid insecticides (acetamiprid, imidacloprid, thiacloprid and thiamethoxam), widely used to manage pests on different crops, and their effects on locomotion of the bee. Neonicotinoids with the cyano radical caused lower bee mortality (assessed by mean lethal concentration, LC50), while those compounds with the nitro radical were highly harmful to T. angustula. Locomotion activity was strongly impaired in bees treated with thiacloprid and imidacloprid, while acetamiprid did not affect the locomotion activity, which was similar to the control. Application of thiamethoxam caused hyperactivity, as observed by increases of ∼4.5 and 5.0-fold in mean speed and distance traveled, respectively. These results suggest that applications of neonicotinoid insecticides can negatively affect the pollination activity of T. angustula. These results can also help to develop strategies to conserve these pollinators in agroecosystems. •The impact of four neonicotinoids was assessed on Tetragonisca angustula.•All neonicotinoid insecticides caused high oral acute toxicity for stingless bees.•Imidacloprid and thiacloprid reduced the locomotion activity of the bee.•Acetamiprid did not cause changes in the locomotion activity of the bee.•Thiamethoxam induced high hyperactivity for stingless bees.